A influência das variáveis climáticas na produção de café arábica (Coffea Arabica L.) no estado de São Paulo nos anos de 1995, 1998 e 2008 - Milani, Camila Giolo [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The coffee culture had great influence on the settlement and economical development of the State of São Paulo. The arrival of coffee with the European current migration streamlined and changed the economy of São Paulo until today. The climate suitability of coffee takes into consideration it's thermal and water requirements. The weather phenomena El Niño and La Niña are phenomena that affect the temperature and rainfall regimes during the months of their occurrence. For the agriculture is important to know the characteristics and impacts of these phenomena so a better planning is done and the prevention of damage is expected. The present study examined the influence of the climate variables and phenomena El Niño and La Niña in the production of Arabic coffee in the State of São Paulo for the years 1995, 1998 and 2008 by making maps and water balance. The aptitude of the state for the coffee culture has been proved and interference of the phenomena El Niño and La Niña in the production of coffee in the state were not noticed.

A cultura do café teve grande influência no povoamento e desenvolvimento econômico do Estado de São Paulo. A chegada do café juntamente com a corrente imigratória vinda da Europa dinamizou e mudou a economia paulista até o presente momento. A aptidão climática do café leva em consideração suas exigências hídricas e térmicas. Os fenômenos climáticos El Niño e La Niña são fenômenos que interferem nas médias térmicas e de precipitação pluvial durante os meses de sua ocorrência. Para a agricultura é válido conhecer as características e impactos causados por estes fenômenos para que um melhor planejamento seja efetuado e a prevenção de danos seja prevista. O presente trabalho analisou a influência das variáveis climáticas e dos fenômenos El Niño e La Niña na produção de café arábica no Estado de São Paulo nos anos de 1995, 1998 e 2008 através da confecção de mapas e balanços hídricos. A aptidão do estado para a produção cafeeira foi comprovada e não foram notadas interferências dos fenômenos climáticos El Niño e La Niña na produção de café do estado.
Keywords: Café - Cultivo - São Paulo (Estado); El NiNo, Corrente; Climatologia agricola